Maqashid Syariah Review of Payment of Workers' Wages in the Self-Help Housing Stimulant Assistance Program (BSPS) in Teluk Pakedai District - Aiyub Anshori; M. Khairul Anwari; Rahmat Rahmat; Amrin Amrin (IHSA Institute, 2024)
The aim of this research is to raise the issue of wage payment schemes. Based on the data, there are still many people who pay wages using a process that is not in accordance with the contract that has been determined, and there are still many people who make wage payments without paying attention to the appropriate time period and amount of wages. So in this research we will discuss how the implementation of worker wage payments in the self-help housing stimulant assistance program (BSPS) is appropriate from a Maqashid Syariah perspective. The government has a program to eradicate uninhabitable housing with a housing assistance program for low-income communities through the PUPR ministry. West Kalimantan, especially Kuburaya district, is in the spotlight with a larger aid allocation quota than other districts. This assistance was in the form of money which was then spent collectively by the beneficiaries amounting to twenty million, with details of seventeen million five hundred thousand for building materials and two million five hundred thousand for workers' wages. Wage payments are made after the house is built by the beneficiary with their own self-sufficiency, so a problem arises in the payment of workers' wages which is deferred until the house is completely built and still has to wait for the entire group to complete its obligations as a condition for paying workers' wages. Based on Maqashid Syariah's review, the process of paying wages in the BSPS program is seen from the indicators of protecting religion, protecting the soul, protecting offspring, protecting property, protecting, and reason. These are not all contradictory, but need to be reviewed from the perspective of dharuriyyat, tahsiniyyat, hajjiyat